Privacy, regulations, and cybersecurity : the essential business guide - Moschovitis, Christos J. P. (John Wiley & Sons, Inc., 2021)
"This book answers the question: How do businesses effectively respond to the evolving definition of privacy through their strategies, operations, cybersecurity posture, and adaptation to new regulations? The book walks the reader through privacy, it's definitions and implications; data regulation, and its increasing impact on business; and cybersecurity as a newly critical business practice. In addition, the book addresses the overarching significance of privacy for companies' overall strategies. There will be numerous examples and case studies that break down every element of the privacy -- regulation -- cybersecurity triad for the executive. It will help executives understand the concepts of privacy, personally identifiable information, definitions and world-wide regulations. The book walks through how to use core risk management principles, evaluate threats, deploy policies and standards, and identify the right tools, roles, and methods for companies to employ."- Resumé vydavatele